Analisis Nilai-Nilai Pragmatik Cerita Rakyat Suku Sasak “Tiwoq-Iwoq” - Pipit Aprilia Susanti (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
Analysis of pragmatic values in the folktale of Sasak tribe named “Tiwoq-Iwoq” which based on some factors there are, the introduction on local literature which has been decrease lately, the existence of the folktale which started to be left on since there are new stories arise and the sink of moral value in young generations. This research aimed at knowing the pragmatic values in Sasak tribe ‘Tiwoq-Iwoq’ folktale. This is a descriptive qualitative research and used library research, documenter, observation, and notes as method of gathering the data. To analyze the research, the researcher uses pragmatic analysis. Based on the analysis it can be concluded that the Sasak Tribe ‘Tiwoq Iwoq’ folktale contains education values such as moral, social, and religious.